Peningkatan Mutu Pendidikan melalui Penerapan Total Quality Management dalam Program Akreditasi Sekolah - Lailatul Azizah; Silvia Witri (Mafapress bekerja sama dengan Prodi PGMI Fakultas Tarbiyah IPMAFA Pati, 2021)
Improving the quality of education is a problem that is still experienced by many educational institutions. To improve the quality of education, institutions need a system to help achieve quality education quality. So this study aims to analyze the application of Total Quality Management in the school accreditation program as an effort to improve the quality of education. This research is a literature study by taking data from several books and literature. This data collection technique uses documentation techniques and data analysis techniques using critical analysis which is interesting from several research documents. The results of this study indicate that improving the quality of education is carried out by implementing Total Quality Management. Total Quality Management is carried out by continuous improvement, determining quality standards, changing culture, changing organizations, maintaining relationships with customers and focusing on customer satisfaction. and have a commitment to change.